Interpretation of inter-ethnic relations in the Ferghana Valley from political aspects - Rakhmonali Begalievich Bekmirzaev (Peerian Journals Publishing, 2022)
This article analyzes the historical and political factors affecting interethnic relations in the Fergana Valley and assesses their role in regional security
Keywords: Central Asia's; interethnic relations; historical and political issues